Interaction of Adipose-Derived Stromal Cells with Breast Cancer Cell Lines. Issue 2 (August 2019) - Teufelsbauer, Maryana; Rath, Barbara; Moser, Doris; Haslik, Werner; Huk, Ihor; Hamilton, Gerhard
Abstract : Background: Assisted lipotransfer for breast reconstruction involves the isolation and supplementation of adipose-derived stromal cells. This procedure has raised concerns regarding safety with respect to promotion of tumor growth and relapse. Several in vitro and animal experimental studies have indicated increased survival, growth, and invasive characteristics of breast cancer cells on interaction with adipose-derived stromal cells. These results seem to be in poor concordance with clinical observations of a low rate of cancer recurrences after assisted lipotransfer. Methods: The authors investigated the effects of adipose-derived stromal cells and adipose-derived stromal cells differentiated into adipocytes and fibroblasts on five breast cancer cell lines (i.e., T47D, MCF-7, BT20, MDA-MB-231, and ZR-75-1) and MCF-10A, a nonmalignant counterpart. Results: Conditioned media of adipose-derived stromal cells stimulated the proliferation of breast cancer cell lines depending on the individual adipose-derived stromal cell–breast cancer cell line combination. Conditioned media of adipose-derived stromal cells differentiated into adipocytes gave a lower response, and conditioned media of fibroblasts were also active. A putative cancer stem cell–like phenotype was not increased by adipose-derived stromal cell–conditioned media, no physical interaction of cancer cells with adipose-derived stromal cells was detectable on scanning electron microscopy, and cell migration was not enhanced. Adipogenic differentiation of adipose-derived stromal cells indicated that hepatocyte growth factor, insulin-like growth factor-binding protein -3, insulin-like growth factor-binding protein -6, interleukin-6, CCL2/MCP-1, and macrophage colony-stimulating factor are not linked to the proliferative activity of conditioned media. Conclusion: The results indicate that the adipose-derived stromal cells used for assisted lipotransfer are not expected to increase the risk of tumor recurrence to a major degree in correspondence with the clinical observation of the affected breast cancer patients. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, V.